Differential geometry of the Z3-graded quantum superplane - Çelik, S (IOP PUBLISHING LTD, 2002)
In this work, differential geometry of the Z(3)-graded quantum superplane is constructed. The corresponding quantum Lie superalgebra and its Hopf algebra structure are obtained.
Keywords: CALCULUS; SUPERGROUP; Physics